La desescritura del dolor en la obra de Mario Bellatin - Goldchluk, Graciela (2017)
The chapter analyzes the disaffection present in voice that assumes the writing of Mario Bellatin as an ethical position that is a constituent part of his poetics. On the one hand, Bellatin seems to tell us, society has decided what events should horrify her and which should not. Certain widely accepted actions are discovered as aberrant when the evaluative layer that protects them is removed. On the other hand, writing refuses to be the bearer of a new evaluation that crystallizes them as negative, thus founding a higher morality. In this way, his position is both ethical and aesthetic and to analyze it I will try to read the subtractive gesture that founds the Bellatinian writing. In a work as broad as that of this Mexican writer who began publishing in Lima, I will focus on two moments: the first will be the scriptural beginning as a concrete action of subtraction followed through its manuscript archive. The second moment will be centered on a reading of La escuela del dolor humano de Sechuán in dialogue with Regarding the Pain of Others, Susan Sontag, to observe the weather that leaves us the work of Bellatin: without the shelter of a reassuring literature that allows us to identify ourselves with a good conscience, the decision to continue writing, like the one to continue reading, demand the recognition that the pain is alien to us as long as we do not do something to remedy it.